Climate change impacts on temperature and chill unit trends for apple (malus domestic) production in Ceres, South Africa - Tharaga, Phumudzo; Steyn, Abraham Stephanus; Coetzer, Gesine Maria (MDPI, 2021)
Climate is an essential part of crop production, determining the suitability of a given region for deciduous fruit products such as apples (Malus domestica). It influences the yield and quality of fruits. There is strong evidence of global and regional-scale climate change since the advent of the industrial era. In South Africa, mean surface temperatures have revealed a warming trend over the last century. This study aimed to assess the impact of climate change on temperature and chill unit trends for apple production in Ceres, South Africa. The daily positive Utah chill units (DPCU) model was used as frequent high temperatures can lead to a high negation volume. Historically observed (1981–2010) and future projected (2011–2100) temperatures were obtained from the South African Weather Service (SAWS) and three ensemble members of the Cubic-Conformal Atmospheric Model (CCAM), respectively. The latter employed the RCP8.5 pathway. Linear trends were calculated for temperature and accumulated PCUs for the historical base period. The probability of accumulating specific threshold PCU values for both historical and future periods was assessed from cumulative distribution functions (CDFs). The historical change in minimum temperatures showed no significant trend. Ceres revealed a warming trend in maximum temperatures over the historical period. By the 2080s, the probability of not exceeding a threshold of 1600 PCUs was exceptionally high for all ensemble members. Future projections showed a decline in the accumulated PCUs of 2–5% by the 2020s, 7–17% by the 2050s, and 20–34% towards the end of the 20th century. Based on these results, it is clear that winter chill units are negatively influenced by climate change. The loss in yield and fruit quality of apples due to climate change can negatively impact the export market, leading to significant economic losses for apple production in the Ceres area.
Keywords: Climate model; Daily positive; Utah chill unit model; Temperature trends; Apple; Malus domestica